DIALEKTOLOGI BAHASA MELAYU DI PESISIR KABUPATEN BENGKAYANG - ., Patriantoro; ., Sumarlan; Fernandez, Inyo Yos (Universitas Muhammadiyah Surakarta, 2012)
This research discusses the dialectology of Malay used by the people in the coastal area of Bengkayang. Particulary those who live in the downstream area of the river. Malay has been used by a great number of people who reside in the coastal area. This research employs quantitative as well as qualitative research method. The data are collected trought the use of in-depth interview method and elicitation technique by directly showing the picture, pointing the reeal objects, or explaining the intended activities. The synchronic method is used to analyze the dialectology of Malay, and the diachronic comparative method is used to help with the analysis of the language reconstruction. The dialectometry is used to figure the percentage of lexicon differences between the reseaech area. The top down reconstruction technicque serves as the way ti analize the data to find the retention and innovation forms. The lexicon differences in different areas are calculated by applying the triangular or poligones de thiessen. The result of the data analysis area 1-2, 1-3, 2-3, 2-4, 3-4 hold under 21% lexicon differences with indicates that they share the same and not different. In the areas whwre the research is conducted, some the relic forms of the proto-language are still found, as well as the innovation forms and the borrowing.